UJI AKTIVITAS ANTIOKSIDAN TEH SEDUHAN DAUN ROSEMARY (Rosmarinus officinalis L.) DAN DAUN STEVIA (Stevia rebaudiana) DENGAN PERBANDINGAN (60:40) - Mercyska, Mercyska Suryandari; Nur Indahwati, Sephia; Gondo Kusumo, , Galuh (Jurnal Komunitas Farmasi Nasional, 2023)
Rosemary is an herbal plant whose content has compounds. Antioxidant that can prevent the occurrence of damage due to free addiction. This study wanted to find out the content of antioxidant that are obtained in steeping rosemary tea with using additional weetener stevia leaves. Antioxidant testing of leaf steeping tea. Rosemary and stevia leaves using the DPPH method observations were conducted at a wavelength of 522 nm, using a Vitamin C comparator. Replication was performed 3 times the treatment with a difference in brewing time of 5 minutes, 10 minutes and 15 minutes. From the results of the stury and observations obtained % Vitamin C concentration 1 ppm 15.45%, concentration 2 ppm 13.18%, concentration 3 ppm 26.52%, concentration 4 ppm 28.79%, concentration 5 ppm 38.33%. As for the result of % steeping rosemary leaf tea and stevia leaves on sample A brewed for 5 minutes on average % soaking 46.83%, sample B brewing for 10 minutes on average 32.01% dampening, and 15 minutes samle C brewing average % dampering 38.8%. The results of the antioxidant activity test of tea steeping rosemary leaves and stevia leaves in a ratio of (60:40) are that there is a strong antioxidant activity.